Peran Polresta Sidoarjo Dalam Penerapan Penegakan Hukum Operasi Yustisi Untuk Meningkatkan Kepatuhan Protokol Kesehatan Covid-19 Pada Masyarakat Di Kabupaten Sidoarjo - Naura Chairunnisa Sigit; Ertien Rining Nawangsari (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Sidoarjo Police is a State apparatus institution with authority to enforce the law in the Sidoarjo Regency area and related to improving the discipline of health protocols, which is a policy of the central government and local governments Sidoarjo Police are tasked with supporting the realization of the program. This study aimed to determine the role of the Sidoarjo Police in implementing judicial operations law enforcement to improve compliance with the Covid-19 health protocol in the community in the Sidoarjo Regency. This study used the descriptive qualitative method. The results of this study are 1). In carrying out its role during the Covid 19 pandemic, the Sidoarjo Police carried out the main tasks of the Police in their working area. 2). In carrying out its role as an agency tasked with maintaining environmental stability and order, the Sidoarjo Police often coordinates with the TNI and local governments to carry out orders, patrol, guard and regulate locations that have the potential to create crowds. 3). In carrying out its role as an agency tasked with law enforcement, the Sidoarjo Police often conduct inspections of locations that have the potential to cause mass gatherings. 4). In carrying out its role as an agency that serves as a protector and public servant, the Sidoarjo Police always move to the villages to share masks and necessities in turn to the underprivileged and always give an appeal to always comply with health protocols.